BANKRUPTCY RISK MODELING AND STRATEGIC ANTI-CRISIS MANAGEMENT IN THE HOTEL AND RESTAURANT BUSINESS IN CONDITIONS OF ECONOMIC INSTABILITY (Development Service Industry Management, 2025)
The article is devoted to the study of current problems of modeling bankruptcy risks and developing strategic anti-crisis measures for hotel and restaurant businesses (HoReCa) in conditions of economic instability. Given the high sensitivity of this sector to external economic fluctuations, in particular inflation, recession, changes in consumer preferences and geopolitical risks, the critical need to improve risk management methods was emphasized. The article analyzes the latest scientific research and publications in this field, which allowed to identify a number of unresolved issues. In particular, the specifics of modeling bankruptcy risks in conditions of hybrid economic instability, characterized not only by cyclical fluctuations, but also by structural changes caused by the pandemic, geopolitical conflicts and technological shifts, have not been sufficiently studied. The article presents tables with risk classification, modeling methods and key indicators, which allows readers to get a clear idea of the main aspects of the study. Particular attention is paid to the analysis of financial ratios, stress testing and VAR models, which are critically important for assessing the financial stability of HoReCa enterprises. In addition, the authors consider the main elements of anti-crisis management, such as financial recovery, operational optimization, marketing adaptation, human resources management, risk management and strategic planning. A structural model of the anti-crisis management system is presented, which reflects the key elements and the relationships between them. The article contains practical recommendations for the application of the anti-crisis management procedure, including the implementation of production and technical measures, the use of external and internal reserves to restore profitability and avoid bankruptcy. The results of the study can be used to increase the competitiveness of HoReCa enterprises, minimize the negative consequences of economic crises and ensure the stable functioning of the industry as a whole. The article will be of interest to scientists, practitioners and students who are interested in issues of risk management and anti-crisis management in the hotel and restaurant business.
Keywords: risk modeling; bankruptcy; crisis management; hotel and restaurant business; economic instability; financial risks; strategic planning